LOCATION ADVANTAGE AND GEORGIA’S POTENTIAL TO ATTRACT FOREIGN DIRECT INVESTMENT - David Sikharulidze; Vasil Kikutadze (European Scientific Journal, ESJ, 2014)
This paper reviews one of the elements of Dunning’s eclectic paradigm to explain the role of location-specific (L) advantages as determinants of foreign direct investment location. OLI paradigm is a general framework which explains that foreign direct investment (FDI) takes place according to three factors: ownership advantage, location advantage and internalization advantage. Location advantages try to explain why a firm should want to locate in a foreign country. Multinational enterprise will typically engage its foreign production when they find it to be in their best interest to combine their ownership advantages and certain internalization gains with production in foreign country. This paper analyzes the location advantages of Georgia to explain the inflow of FDI to Georgia’s economy. It also analyzes the motive behind FDI in Georgia. These motivations serve to determine what policies the host country should pursue in order to facilitate the location of FDI in Georgia’s economy.